Perbandingan Metode Net, Gross, dan Gross Up dalam Strategi Penghematan Pajak Terutang Perusahaan - Dewi Sartika; Muhammad Arief (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
Tax is a primary source of funding for development in Indonesia, collected in accordance with applicable regulations. For taxpayers, taxes represent a burden that diminishes income, leading them to optimize this burden through tax planning, particularly regarding Article 21 Income Tax. Taxpayers are classified into corporate and individual categories, employing three tax planning methods the Net method, the Gross method, and the Gross Up method. This study aims to identify the impact of the Article 21 withholding method on taxpayers obligations. The findings indicate that the gross method is the most efficient approach for managing the company’s tax burden. In contrast to the net and gross-up methods, using the gross method means the company assumes the employees’ tax burden, resulting in a lower net profit for the company.